2006
DOI: 10.1080/13546800444000308
|View full text |Cite
|
Sign up to set email alerts
|

Insight, symptoms and executive functions in schizophrenia

Abstract: The findings of partial association between dimensions of insight and measures of executive function supports the growing evidence that insight is a multidimensional phenomenon. Accordingly, they emphasise that in the framework of therapeutic interventions, enhancement of higher levels of insight needs to take into account that patients suffering from schizophrenia have differential impairment in insight dimensions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
11

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 52 publications
1
12
0
11
Order By: Relevance
“…In recent years a growing number of researchers have suggested that schizophrenia is fundamentally a disease of neuropsychological dysfunction and that previous research has over-emphasized clinical symptomotology (Gold and Harvey, 1993;Mohamed et al, 1999aMohamed et al, , 1999bKeefe et al, 2003). Some studies have reported a significant association between impaired insight and executive functioning (Drake and Lewis, 2003;Simon et al, 2006;Monteiro et al, 2008), memory (Smith et al, 2000;Rossell et al, 2003;Keshavan et al, 2004) or attention (Lysaker and Bell, 1995). Imaging studies have found dysfunction in cortical areas, which are believed to support these neurocognitive functions, and are also potentially linked with deficits in insight (Raij et al, 2012).…”
Section: Introductionmentioning
confidence: 93%
“…In recent years a growing number of researchers have suggested that schizophrenia is fundamentally a disease of neuropsychological dysfunction and that previous research has over-emphasized clinical symptomotology (Gold and Harvey, 1993;Mohamed et al, 1999aMohamed et al, , 1999bKeefe et al, 2003). Some studies have reported a significant association between impaired insight and executive functioning (Drake and Lewis, 2003;Simon et al, 2006;Monteiro et al, 2008), memory (Smith et al, 2000;Rossell et al, 2003;Keshavan et al, 2004) or attention (Lysaker and Bell, 1995). Imaging studies have found dysfunction in cortical areas, which are believed to support these neurocognitive functions, and are also potentially linked with deficits in insight (Raij et al, 2012).…”
Section: Introductionmentioning
confidence: 93%
“…[21] The most researched symptom dimensions in schizophrenia are positive, negative and cognitive dimensions. Some of the previous studies have demonstrated relationship of insight with positive symptoms,[222324252627] negative symptoms,[22252627282930313233] and neurocognitive impairment[34] among patients with schizophrenia.…”
Section: Insight and Its Relationship With Symptom Dimensions In Schimentioning
confidence: 99%
“…Several factors have emerged to be associated with insight such as the neurocognitive performance [51], the patients’ psychopathology [48] or the level of functioning [14]. Impairments in insight are believed to be mediated by deficiencies in conceptual disorganization and flexibility in abstract thinking [49] and Aleman et al reported in their meta-analysis that impairments of set-shifting and error monitoring also contribute to poor insight [1].…”
Section: Introductionmentioning
confidence: 99%